Influência de águas de reuso na hidratação, trabalhabilidade e comportamento mecânico de matrizes cimentícias - D’Hyppolito Filho, Julio Cezar (2019)
The current scenario of water crisis and the fact that water is an essential input in concrete suggests the need to study sustainable alternatives to replace drinking water in concrete in order to reduce its water footprint. In this context, wastewater reuse is presented as a good alternative, since sewage treatment plants return effluents with a high degree of purification. This study presents the advanced effects of using two different types of reused wastewater from sewage treatment, with different treatment levels, as mixing water and curing water in concrete. The research focused on the effects associated with hydration kinetics, workability and mechanical behavior in concrete, as well as the characterization of reuse wastewaters. In the results, it can be observed that the reuse wastewaters presented a behavior very similar to the drinking water, indicating the viability of substitution in the activities related to the concrete production, as well as its cure.